Implementation of Limited Face-to-face Learning Policy in the New Normal Era of the Covid-19 Pandemic - Atie Mujiarti; Seni Apriliya; Erwin Rahayu Saputra (Indonesian Journal of Primary Education, 2022)
The purpose of this study Implementation of Limited Face-to-face Learning Policy in the New Normal Era of the Covid-19 Pandemic all countries affected by the Covid-19 pandemic are currently adapting so that the pandemic does not have a much worse impact on all aspects of life. People definitely have to adapt to new habits in the order of their activities, not least in the world of education. The Minister of Education through Joint Decision of 4 Ministers lowered the policy on Limited Face-to-face Learning in the New Normal Era. Each education unit has its own challenges in implementing policies regarding education in the era of adapting new habits. This study aims to analyze the policy of Limited Face-to-face Learning Implementation in the New Normal Era at the Ciamis District Elementary School and its implementation. The method used for this research is descriptive qualitative. The research was conducted at the State Elementary School in Ciamis District. The key informant at each school was the Class Teacher who carried out Limited Face-to-face Learning Activities during the New Normal. The research in instruments used were field observations, interviews and documentation. The results showed that the Limited Face-to-face Learning policy in the New Normal era at the State Elementary School in Ciamis District had been successfully implemented, although there were several factors that needed to be improved and re-evaluated. The implementation of the Limited Face-to-face Learning process at public elementary schools in Ciamis District can be carried out through various school policies that are carried out explicitly through the preparation of facilities and infrastructure that must be prepared for limited face-to-face learning and preparing a curriculum for special conditions to facilitate teachers in conducting effective learning.